ANALYSIS OF FACTORS INFLUENCING LABOR QUALITY IN THE HANDICRAFT SECTOR OF BAC NINH - Tung, Pham; Thuận, Ngô; Anh, Nguyen (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
This research investigated the main factors that influence labor quality in the handicraft sector of Bac Ninh province. A total of 261 laborers in this sector were interviewed according to 48 various aspects of labor quality. Exploratory factor analysis was employed to group different variables and a regression model was used to predict the impact of the main factors on the quality of labor. Seven different factors were extracted from the factor analysis, including employee welfare policies, working conditions, career opportunities, education and training, remuneration, facilities and equipment, and health care system. The regression results showed the positive impact of these factors on the quality of handicraft laborers. In order to enhance the quality of handicraft laborers, the local government as well as the handicraft firms should improve the employee working conditions, provide more appropriate education and training programs, and pay more attention to employee welfare and career opportunities. Remuneration, facilities and equipment, and health care system were evaluated at acceptable levels by all respondents.